Photodynamic polymers constituted by porphyrin units as antibacterial materials - Ballatore, María Belén (2022)
Photodynamic inactivation of microorganisms has emerged as a promising strategy to killand eradicate pathogens. In this work, two polymers, TCP-P and ZnTCP-P, were synthesized byoxidative polymerization of 5,10,15,20-tetrakis [3-(N-ethylcarbazoyl)]porphyrin and its complex withZn(II). Solid polymers consist of rods (diameter 100 nm, length ~100–500 nm) that form microporous structures on a surface. UV-visible absorption spectra in solution showed the Soret and Q bands characteristic of the corresponding constitutional porphyrins. In addition, the polymers presented two red emission bands with quantum yields 0.11 for TCP-P and 0.050 for ZnTCP-P. These compounds sensitized the production of singlet molecular oxygen with quantum yields of ~0.3. Thus, the spectroscopic and photodynamic properties of the porphyrin units were maintained in the conjugates. The photodynamic activity induced by both polymers was tested to inactivate S. aureus. In cell suspensions, TCP-P was more effective than ZnTCP-P in killing bacteria. Viable S. aureus cells were not detected using 4 microM TCP-P after 20 min of irradiation. Moreover, both polymers showed a high photocytotoxic activity to eradicate S. aureus cells attached to a surface. The results indicate that these conjugated polymers can act as effective antimicrobial agents to photoinactivate pathogens.